Changes in left ventricular stroke volume measured by Doppler echocardiography. Issue 4 (October 1985) - Ihlen, H; Myhre, E; Pamlie, J; Forfang, K; Larsen, S
Abstract : Cardiac stroke volume was measured simultaneously by Doppler echocardiography and thermodilution in 20 patients with coronary artery disease. Stroke volume as determined by ultrasound was calculated from the area of the aortic orifice and the flow velocity just distal to the aortic cusps. The recordings were made twice at rest. Ten patients were given dobutamine (2.5 and 5.0 micrograms/kg/min) by infusion to induce rapid changes in stroke volume from the resting state. The individual Doppler data before, during, and after dobutamine infusion correlated closely with the thermodilution data (r = 0.92). These results suggest that Doppler echocardiography reliably detects changes in stroke volume.